Examining the relationship between stakeholders focus and company performances: some empirical evidences from Malaysian business firms - Fazli Idris; Khairul Anuar Mohd Ali; Norsiah Aminudin (Penerbit Universiti Kebangsaan Malaysia, 2010)

(untitled)
This paper investigates the relationship between stakeholder focus capability; an important internal organisational capability with company performances. Stakeholder theory reflects that the firms’ performance will depend on how organisations balance the needs of their stakeholders. Meanwhile, TQM model, while recognising the stakeholders needs, limits the scope to only few vital groups. Furthermore, TQM model specifies the internal capability to focus on important stakeholders and therefore we shall use TQM as our research framework. This study focuses on three important stakeholders; customer, employee, and community because of their direct relationship with business outcomes. An instrument is developed to measure the related constructs and is found to be reliable. Using exploratory factor analysis, we found that the items clearly group into the three factors; customer focus, employee focus, and community focus. Another factor analysis on the company performance measure results in a single factor. We proceed with the multiple regression analysis to test the relationship between the dependent, company performances and the independent factors, the three dimensions of stakeholder focus capability. The percentage variance explained by the three factors is 68 percent. Customer, community and employee focus significantly influence the company performances with beta coefficient of 0.563, 0.465, and 0.424 respectively. The relationship is moderated by the company size with large companies is observed to have a higher ability to focus. We conclude that emphasis on these three groups are important thus developing the capability to focus on them must be given due consideration. Theoretical and practical implications are discussed